Risk and stigma: students' perceptions and disclosure of 'disability' in higher education. (15th November 2018) - Eccles, Sue; Hutchings, Maggie; Hunt, Clive; Heaslip, Vanessa
There is a focus on increasing the numbers of students with disabilities who apply to and study in Higher Education (HE). Despite sector-wide criteria regarding what comprises a disability, there are still students who do not disclose a disability at the application stage. This study sought to explore perceptions of students across one UK university regarding their views and experiences of a range of disabilities and reasons why a disability may not be disclosed on application to HE. The [mdings suggest a lack of understanding regarding what constitutes a disability, and concerns that disclosure will negatively impact upon the application decision and disadvantage the student. This paper highlights the disconnect between the support that universities can provide to students with a disability and the perceptions that some students have about the disadvantages that disclosure can bring. The findings support initiatives at policy and practice level across the sector to recognise and address perceptions and experiences of risk and stigma that applicants may have but at the same time the findings highlight that more needs to be done to reduce the anxieties and lack of clarity that some students experience.